Streptococcus pyogenes Causing Skin and Soft Tissue Infections Are Enriched in the Recently Emerged emm89 Clade 3 and Are Not Associated With Abrogation of CovRS - Pato, Catarina; Melo-Cristino, José; Ramirez, Mario; Friães, Ana; , The Portuguese Group for the Study of Streptococcal Infections; Vaz, Teresa; Gião, Marília; Ferreira, Rui; Silva, Ana Cristina; Costa, Hermínia; Silva, Maria Fátima; Afonso, Maria Amélia; et al. (Frontiers in Microbiology, 2018)
Although skin and soft tissue infections (SSTI) are the most common focal infections associated with invasive disease caused by Streptococcus pyogenes (Lancefield Group A streptococci - GAS), there is scarce information on the characteristics of isolates recovered from SSTI in temperate-climate regions. In this study, 320 GAS isolated from SSTI in Portugal were characterized by multiple typing methods and tested for antimicrobial susceptibility and SpeB activity. The covRS and ropB genes of isolates with no detectable SpeB activity were sequenced. The antimicrobial susceptibility profile was similar to that of previously characterized isolates from invasive infections (iGAS), presenting a decreasing trend in macrolide resistance. However, the clonal composition of SSTI between 2005 and 2009 was significantly different from that of contemporary iGAS. Overall, iGAS were associated with emm1 and emm3, while SSTI were associated with emm89, the dominant emm type among SSTI (19%). Within emm89, SSTI were only significantly associated with isolates lacking the hasABC locus, suggesting that the recently emerged emm89 clade 3 may have an increased potential to cause SSTI. Reflecting these associations between emm type and disease presentation, there were also differences in the distribution of emm clusters, sequence types, and superantigen gene profiles between SSTI and iGAS. According to the predicted ability of each emm cluster to interact with host proteins, iGAS were associated with the ability to bind fibrinogen and albumin, whereas SSTI isolates were associated with the ability to bind C4BP, IgA, and IgG. SpeB activity was absent in 79 isolates (25%), in line with the proportion previously observed among iGAS. Null covS and ropB alleles (predicted to eliminate protein function) were detected in 10 (3%) and 12 (4%) isolates, corresponding to an underrepresentation of mutations impairing CovRS function in SSTI relative to iGAS. Overall, these results indicate that the isolates responsible for SSTI are genetically distinct from those recovered from normally sterile sites, supporting a role for mutations impairing CovRS activity specifically in invasive infection and suggesting that this role relies on a differential regulation of other virulence factors besides SpeB.